To Bangkok and beyond - Potter, Michael Paul. (Melbourne: Lansdowne Press, 1970)
An introduction to the history, geography, cities, people, religion, and customs of Thailand.
Stamped on t.p.: Distributed by Sportshelf, New Rochelle, N.Y.
Keywords: Thailand -- Description and travel -- 1951 -- 1975 -- Juvenile literature